Kualitas Pelayanan E Government dalam Pelaksanaan Pelayanan Publik di Perpustakaan Soeman HS Provinsi Riau - Vina Yolanda Putri; Zulkarnaini Zulkarnaini (Lembaga Pengembangan Kinerja Dosen, 2026)
Advances in information and communication technology have encouraged governments to integrate digital systems into public service delivery through e-government initiatives. In Riau Province, the Riau application at the Soeman H.S. Library exemplifies this implementation. This study examines how the Riau application enhances the effectiveness and efficiency of public services within the library. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. Findings show that the application provides convenient online access to library information and services. However, challenges remain, including limited financial resources, dependence on external parties, and insufficient feature development to meet user needs fully. These findings underscore the importance of strengthening institutional capacity, improving infrastructure, and formulating strategic plans to sustain digital library services. In line with Indonesia’s 1945 Constitution, regional governments possess autonomy to manage local affairs, aiming to improve public welfare through enhanced services, community empowerment, and civic participation while promoting regional competitiveness with attention to equity and democratic values. Following Presidential Instruction No. 3 of 2003, digital governance transformation is necessary to reduce bureaucratic barriers, integrate workflows, and support inter-institutional collaboration.